The Future of Employment: Purposive Interpretation and the Role of Contract after Uber. Issue 3 (21st September 2021) - Atkinson, Joe; Dhorajiwala, Hitesh
Abstract: A person's entitlement to workplace rights and protections under English law is conditional on their relationship falling within the legal category of employment, by virtue of them having the requisite status. The employment status of individuals performing on‐demand work via digital platforms is particularly contentious and has been a focal point for debate in recent years. The Supreme Court decision in Uber BV v Aslam represents a ground‐breaking judgment on this issue, which has radical implications for the correct approach to determining employment status more generally. It is argued here that, while leaving some important questions unanswered, the purposive and relational approach to employment status developed by the Supreme Court in Uber BV v Aslam is to be welcomed, and that this new approach has far‐reaching consequences for the future of the legal category of employment.